The pilgrim art : cultures of porcelain in world history - Finlay, Robert (The California world history library, 2010)
Illuminating one thousand years of history, The Pilgrim Art explores the remarkable cultural influence of Chinese porcelain around the globe. Cobalt ore was shipped from Persia to China in the fourteenth century, where it was used to decorate porcelain for Muslims in Southeast Asia, India, Persia, and Iraq. Spanish galleons delivered porcelain to Peru and Mexico while aristocrats in Europe ordered tableware from Canton. The book tells the fascinating story of how porcelain became a vehicle for the transmission and assimilation of artistic symbols, themes, and designs across vast distances-from Japan and Java to Egypt and England. It not only illustrates how porcelain influenced local artistic traditions but also shows how it became deeply intertwined with religion, economics, politics and social identity. Bringing together many strands of history in an engaging narrative studded with fascinating vignettes, this is a history of cross-cultural exchagne focused on an exceptional commodity that illuminates the emergence of what is arguably the first genuinely global culture